PENERAPAN MODELPEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 77 PEKANBARU - Sy. Rohana Sy. Rohana; Jesi Alexander Alim; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of the research is to improve the learning outcomes of students in the subjects of mathematics class II in SD Negeri 77 Pekanbaru by using Cooperative Learning Type STAD (Student Teams Achievement Divisions). This research was conducted by two cycles. Percentage of teachers at meeting the first activity cycle I 79,17% good category, the second meeting 83,33% with categories either. Cycle II first meeting 91,67% by category is very good, the second meeting of the 95,83% with the very good category. The percentage of student activity on the cycle I first meeting 75% category enough, the second meeting of the 79,17% category either. Cycle II first meeting of 87.5% by category is very good, the second meeting 91,67% with very good category. Based on the data analysis and discussion of research results average student learning has increased. The average results of student learning on a base score 66,97, on 74,21, and I cycle on cycle II i.e. 86,27. Based on the results of the study it can be concluded that the application of the Cooperative Learning Model Type STAD (Student Teams Achievement Divisions) can improve Learning ResultsMath Grade II in SD Negeri 77 Pekanbaru.Keywords : Cooperative Learning Model type STAD, Student Achievement The Result of Mathematics Studies.